Effect of an α-Lactalbumin-Enriched Infant Formula Supplemented With Oligofructose on Fecal Microbiota, Stool Characteristics, and Hydration Status: A Randomized, Double-Blind, Controlled Trial. (April 2015) - Wernimont, Susan; Northington, Robert; Kullen, Martin J.; Yao, Manjiang; Bettler, Jodi
Aims . To evaluate the impact of oligofructose (OF)-supplemented infant formula on fecal microbiota, stool characteristics, and hydration. Methods . Ninety-five formula-fed infants were randomized to α-lactalbumin-enriched control formula (CF) or identical formula with 3.0 g/L OF (EF) for 8 weeks; 50 infants fed human milk (HM) were included. Results . Eighty-four infants completed the study, 70 met per-protocol criteria. Over 8 weeks, bifidobacteria increased more in EF than CF group (0.70 vs 0.16 log10 bacterial counts/g dry feces, P = .008); EF was not significantly different from HM group ( P = .32). EF group stool consistency was intermediate between CF and HM groups; at week 8, EF group had softer stools than CF (5-point scale: 1 = hard, 5 = watery; consistency score 3.46 vs 2.82, P = .015) without significant differences in stool frequency. Physician-assessed hydration status was normal for all infants. Conclusions . Infant formula with 3.0 g/L OF promoted bifidobacteria growth and softer stools without adversely affecting stool frequency or hydration.